School-based research a guide for education students - Wilson, Elaine (Elaine Geraldine) (Los Angeles SAGE, 2017)
Focused on the needs of the new classroom researcher, and those studying education on Masters-level courses, this is a thorough and thoughtful guide to the research process, covering qualitative, quantitative and mixed research methods.
Becoming a reflexive teacher -- Refining the focus for research and formulating a research question -- Reviewing literature and writing a literature review -- Research design -- Ethics in educational research -- What is educational action research -- How to do action research -- The case study -- Building theory from data: grounded theory -- Research with younger children: issues and approaches -- data collection -- Reliability in qualitative research by teacher researchers -- Taking a quantitative approach -- Handling data -- Analysing qualitative data -- Analysing quantitative data -- Writing about research -- Disseminating research, blogs and social media -- Beyond positivism -- Interpretivism: meeting our selves in research.
Previous edition : 2012.
Includes bibliographical references and index.
Keywords: Education -- Research